Lupus Cerebritis Refractory to Guideline-Directed Therapy: A Case Report - Suman Rao MD; Akhila Sunkara MBBS; Ashwini Ashwath MBBS; Nimisha Srivastava MBBS; Emily Albert MD, MPH (SAGE Publishing, 2021)
Systemic lupus erythematosus is an autoimmune disease that affects multiple organs and organ systems, subsequently requiring an elaborate regimen for management. We present the case of a 63-year-old female who developed unrelenting symptoms of drug-induced lupus, which persisted even after the offending agent was withdrawn, unmasking her underlying systemic lupus erythematosus. She continued to develop neuropsychiatric symptoms, including mania and hallucinations, which complicated the management of her disease. After exhausting the bank of anti-inflammatory and immunomodulators recommended by current guidelines, we found that a combination of rituximab infusions with thiothixene, an antipsychotic agent, significantly improved our patient's neuropsychiatric symptoms. Further research should be conducted to determine the efficacy of rituximab in the treatment of resistant lupus cerebritis, and to validate the use of thiothixene in the management of neuropsychiatric symptoms secondary to lupus.